How Collaborative Approach Works in Supply Chain: Garoto Case Study - Bretas, Marcia Viviane (2008)
ABSTRACT It is well known the focus given by companies on the potential in adding stronger, yet more flexible links to their supply chains in the form of collaborative relationship. Consequently, a large number of researches have been done to understand and figure up the Supply Chain collaboration relationship. This particular study presents a journey to explore how the collaborative approach works in supply chain context, and results operations processes improvement. The research is based on a single case of Garoto, a chocolate manufacture in Brazil. The relevant research background was detailed in terms of supply chain collaborative viewpoint; collaborative environmental preparation; process implementation; and advantages and barriers regarding to this. Then study of a specific supply chain case will be taken into consideration in order to exemplify the theory. Furthermore, the analyses of research results are presented with the objective of extrapolate from theory to practical implication in different sectors. Relevant findings are presented accordingly based on interviews (i.e. structured and non structured interview) a great quantity of key information from the business unit such as documentations (e.g. paper review); direct observation; Internet and libraries consulting. After all, it is noticeable that the following dissertation will primarily address those managers, leaders and partners, who participate in the chain, and are responsible or even involved in improving the supply chain operation through collaborative approach.